Priests, witches and power : popular Christianity after mission in Southern Tanzania - Green, Maia. (Cambridge ; New York : Cambridge University Press, 2003)
In this book, Maia Green explores contemporary Catholic practice in a rural community of Southern Tanzania, and discusses how Christianity has come to have widespread acceptance in Southern Tanzania in the historical context of colonial mission. It will appeal to scholars and students of anthropology, sociology and African Studies.
Cover; Half-title; Series-title; Title; Copyright; Contents; Maps; Preface; 1 Global Christianity and the structure of power; 2 Colonial conquest and the consolidation of marginality; 3 Evangelisation in Ulanga; 4 The persistence of mission; 5 Popular Christianity; 6 Kinshipand the creation of relationship; 7 Engendering power; 8 Women's work; 9 Witchcraft suppression practices and movements; 10 Matters of substance; Notes; References; Index.
Includes bibliographical references (pages 156-167) and index.
Print version record.
Keywords: Catholic Church -- Tanzania -- Ulanga District -- History -- 20th century; Catholic Church; Ulanga District (Tanzania) -- Church history -- 20th century; Ulanga District (Tanzania) -- Religious life and customs; SOCIAL SCIENCE -- Sociology of Religion; Electronic books